Block Copolymer Synthesis by the Combination of Living Cationic Polymerization and Other Polymerization Methods - Dey, Asmita; Haldar, Ujjal; De, Priyadarsi (Frontiers in Chemistry, 2021)
The foremost limitation of block copolymer synthesis is to polymerize two or more different types of monomers with different reactivity profiles using a single polymerization technique. Controlled living polymerization techniques play a vital role in the preparation of wide range of block copolymers, thus are revolutionary techniques for polymer industry. Polymers with good control over molecular weight, molecular weight distribution, chain-end functionality and architectures can be prepared by these processes. In order to improve the existing applications and create new opportunities to design a new block copolymer system with improved physical and chemical properties, the combination of two different polymerization techniques have tremendous scope. Such kinds of macromolecules may be attended by combination of homopolymerization of different monomers by post-modification techniques using a macroinitiator or by using a dual initiator which allows the combination of two mechanistically distinct techniques. This review focuses on recent advances in synthesis of block copolymers by combination of living cationic polymerization with other polymerization techniques and click chemistry.